Assessing oxidative stress in tumors by measuring the rate of hyperpolarized [1-13C] dehydroascorbic acid reduction using 13C magnetic resonance spectroscopy - Timm, KN; Hu, D-E; Williams, M; Wright, AJ; Kettunen, MI; Kennedy, BWC; Larkin, TJ; Dzien, P; Marco-Rius, I; Bohndiek, SE; Brindle, KM (American Society for Biochemistry and Molecular Biology, 2016)
Rapid cancer cell proliferation promotes the production of reducing equivalents, which counteract the effects of relatively high levels of reactive oxygen species. Reactive oxygen species levels increase in response to chemotherapy and cell death, whereas an increase in antioxidant capacity can confer resistance to chemotherapy and is associated with an aggressive tumor phenotype. The pentose phosphate pathway is a major site of NADPH production in the cell, which is used to maintain the main intracellular antioxidant, glutathione, in its reduced state. Previous studies have shown that the rate of hyperpolarized [1-13C]dehydroascorbic acid (DHA) reduction, which can be measured in vivo using non-invasive 13C magnetic resonance spectroscopic imaging, is increased in tumors and that this is correlated with the levels of reduced glutathione. We show here that the rate of hyperpolarized [1-13C]DHA reduction is increased in tumors that have been oxidatively prestressed by depleting the glutathione pool by buthionine sulfoximine treatment. This increase was associated with a corresponding increase in pentose phosphate pathway flux, assessed using 13C-labeled glucose, and an increase in glutaredoxin activity, which catalyzes the glutathione-dependent reduction of DHA. These results show that the rate of DHA reduction depends not only on the level of reduced glutathione, but also on the rate of NADPH production, contradicting the conclusions of some previous studies. Hyperpolarized [1-13C]DHA can be used, therefore, to assess the capacity of tumor cells to resist oxidative stress in vivo. However, DHA administration resulted in transient respiratory arrest and cardiac depression, which may prevent translation to the clinic.